أثر التعويضات على الرضا الوظيفي في المؤسسة دراسة ميدانية في بلدية حساني عبد الكريم بالوادي - إبراهيم زايد; علي زاوش; أمنية زيدي (جامعة الوادي University Of Eloued, 2024)
"هدفت الدراسة إلى التعرف على علاقة التعويضات (المباشرة وغير المباشرة) كمتغير مستقل بالرضا الوظيفي بأبعاده (الراتب والمكافآت، نمط الإشراف، نظام الترقية، محتوى العمل، جماعة العمل، ظروف محيط العمل) كمتغير تابع في بلدية حساني عبد الكريم -الوادي- ولتحقيق أهداف هذه الدراسة قمنا بتصميم استبانه شملت (36) عبارة ووزعنا 96 استبانة تم استرجاع 96 استبانة صالحة للدراسة واستخدمنا المنهج الوصفي التحليلي بالإعتماد على دراسة حالة المؤسسة محل الدراسة باستخدام أسلوب المسح الاجتماعي والاختبارات الإحصائية المناسبة لاختبار صحة الفرضيات وللإجابة عن تساؤلات الدراسة باستخدام الحزمة الإحصائية للعلوم الاجتماعية وتم استخدام العديد من الأساليب الإحصائية ومن ابرز النتائج التي تم التوصل إليها أنه يوجد أثر للتعويضات بأنواعها على الرضا الوظيفي في بلدية حساني عبد الكريم – الوادي. " " The study aimed to identify the relationship of compensation (direct and indirect) as an independent variable to job satisfaction in its dimensions (salary and rewards, style of supervision, promotion system, work content, work group, work environment conditions) as a dependent variable in the municipality of Hassani Abdel Karim - El Oued. To achieve the objectives of this study, we designed a questionnaire that included (36) statements, distributed 96 questionnaires, and 96 valid questionnaires were retrieved for the study. We used the descriptive analytical approach, relying on a case study of the institution under study, using the social survey method and appropriate statistical tests to test the validity of the hypotheses and to answer the study’s questions using the Statistical Package for Science. Social studies and many statistical methods were used One of the most prominent results reached is that there is an impact of all types of compensation on job satisfaction in the municipality of Hassani Abdel Karim - El Oued. "
مذكرة ماستر
Keywords: تعويضات مباشرة، تعويضات غير مباشرة، تعويضات المعنوية، رضا وظيفي، بلدية حساني عبد الكريم – الوادي -.; direct compensation; indirect compensation; moral compensation; job satisfaction; Hassani Abdel Karim Municipality - El Oued -.